Effect of the flame retardant tris (1, 3-dichloro-2-propyl) phosphate (TDCPP) on Na+-K+-ATPase and Cl− transport in HeLa cells. (13th October 2018) - Latronico, Simona; Giordano, Maria Elena; Urso, Emanuela; Lionetto, Maria Giulia; Schettino, Trifone
Abstract: Tris (1, 3-dichloro-2-propyl) phosphate (TDCPP) is one of the most diffused phosphorus flame retardants in the environment and is highly persistent and abundant in residential dust samples. To date the cellular targets and mechanisms underlying its toxic effects are not completely understood. The aim of this work was to study the effects of TDCPP on ion transport mechanisms fundamental for the cellular ionic homeostasis, such as Na + -K + -ATPase and Cl − transport. HeLa cells were used as experimental model. TDCPP showed a dose-dependent effect on cell viability in cells exposed for 24 h as assessed by MTT test (IC50  = 52.5 µM). The flame retardant was able to exert a dose and time-dependent inhibition on the Na + -K + -ATPase activity. A short-term exposure (1 h) was able to exert a significant inhibition at 75 and 100 µM TDCPP, suggesting that TDCPP is able to directly interfere with the Na + -K + -ATPase phosphate catalytic activity. The sensitivity of the pump to lower TDCPP concentrations increased with the increase of the time of exposure. Following 24 h exposure a significant inhibition of about 40% was evident already at 10 µM and the IC50 value observed was 12.8 ± 6.0 µM. Moreover, TDCPP was also able to impair the NKCC mediated Cl − transport in HeLa cells, as assessed in YFP-H148Q/I152L-expressing HeLa cells. Following 1 h exposure TDCPP significantly inhibited the transport by about 30%. The kinetic analysis demonstrated a noncompetitive mechanism of inhibition. In conclusion, results demonstrated the impairment of ion transport mechanisms fundamental for ion homeostasis by TDCPP on HeLa cells.